2019
DOI: 10.33808/clinexphealthsci.600144
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Treatment and Pulp Stone Formation: Is There a Relationship?

Abstract: The aim of this retrospective study was to evaluate the effect of orthodontic treatment on pulp stone formation. Methods: The sample population comprised 504 patients (182 males, 312 females) with a mean age of 17.7 ± 2.9 years that underwent orthodontic treatment. The pre-treatment and post-treatment panoramic radiographs of the patients were evaluated to detect pulp stones before and after orthodontic treatment. The data were analyzed using Mc Nemar, Chi-square and Fisher Exact tests. Results: The statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
(53 reference statements)
4
8
1
Order By: Relevance
“…Assessment of presence of calcifications after orthodontic treatment, by analyzing panoramic radiographs, was performed by Ertas et al (2017), Jena et al (2018), and Korkmaz et al (2019), showed an increase in the incidence of post-treatment PS, which does not corroborate our findings.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…Assessment of presence of calcifications after orthodontic treatment, by analyzing panoramic radiographs, was performed by Ertas et al (2017), Jena et al (2018), and Korkmaz et al (2019), showed an increase in the incidence of post-treatment PS, which does not corroborate our findings.…”
Section: Discussioncontrasting
confidence: 84%
“…In this study, orthodontic treatment was not associated with PS incidence. With a varied and not yet fully elucidated etiopathogenesis, orthodontic movement has proven to be a relevant factor associated with the development of PS according to other authors (ERTAS et al, 2017;JENA et al, 2018;KORKMAZ;AYDIN;SARIOGLU, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations